Regioisomer‐Free Difluoro‐Monochloro Terminal‐based Hexa‐Halogenated Acceptor with Optimized Crystal Packing for Efficient Binary Organic Solar Cells. Issue 46 (17th October 2022) - Yan, Lu; Zhang, Heng; An, Qiaoshi; Jiang, Mengyun; Mahmood, Asif; Jee, Min Hun; Bai, Hai‐Rui; Zhi, Hong‐Fu; Zhang, Shaowen; Woo, Han Young; Wang, Jin‐Liang
Abstract: Herein, we synthesized new hetero‐halogenated end groups with well‐determined fluorinated and chlorinated substitutions ( o ‐FCl‐IC and FClF‐IC), and synthesized regioisomer‐free small molecular acceptors (SMAs) Y‐Cl, Y‐FCl, and Y‐FClF with distinct hetero‐halogenated terminals, respectively. The single‐crystal structures and theoretical calculations indicate that Y‐FClF exhibits more compact three‐dimensional network packing and more significant π‐π electronic coupling compared to Y‐FCl. From Y‐Cl to Y‐FCl to Y‐FClF, the neat films exhibit a narrower optical band gap and gradually enhanced electron mobility and crystallinity. The PM6 : Y‐FClF blend film exhibits the strongest crystallinity with preferential face‐on molecular packing, desirable fibrous morphology with suitable phase segregation, and the highest and balanced charge mobilities among three blend films. Overall, the PM6 : Y‐FClF organic solar cells (OSCs) deliver a remarkable efficiency of 17.65 %, outperforming the PM6 : Y‐FCl and PM6 : Y‐Cl, which is the best PCE for reported hetero‐halogens‐based SMAs in binary OSCs. Our results demonstrate that difluoro‐monochloro hetero‐terminal is a superior regio‐regular unit for enhancing the intermolecular crystal packing and photovoltaic performance of hetero‐halogenated SMAs. Abstract : New fluorine/chlorine regio‐regular hetero‐trihalogenated terminal was firstly synthesized and systematically employed to enhance single‐crystal packing, improve film morphology, and boost device performance of the hetero‐halogenated SMAs. The PM6 : Y‐FClF achieved a remarkable PCE of 17.65 %, which is far better than that of Y‐Cl and Y‐FCl and is the highest efficiency for the hetero‐halogenated SMAs‐based binary OSCs.